1987
DOI: 10.1152/jappl.1987.62.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic involvement in PAF-induced contraction in canine trachealis in vivo

Abstract: We studied the contractile response elicited by platelet-activating factor (PAF) administered intra-arterially into the tracheal circulation of 34 dogs in vivo. A method that avoided tachyphylaxis encountered in prior investigations was developed for isometric measurement of multiple dose-response effects. PAF was a very potent contractile agent; active tension was elicited with 10(-11) mol ia PAF. To determine the mechanism by which contraction was induced, dose-response curves were generated in groups of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
2
8
1
Order By: Relevance
“…In vivo, these cyclooxygenase products may stimulate the afferent pathway of a cholinergic parasympathetic reflex. This hypothesis appears to be supported by our findings on the presumptions that hexamethonium bromide is a specific ganglionic blocker which inhibits the efferent (postganglionic) transmissions (Leff, White, Munoz, Popovich, Shioya & Stimler-Gerard, 1987) and that ipratropium bromide is a specific muscarinic antagonist which inhibits the effects of 'acetylcholine' released at the neuroepithelial junction.…”
Section: Discussionsupporting
confidence: 81%
“…In vivo, these cyclooxygenase products may stimulate the afferent pathway of a cholinergic parasympathetic reflex. This hypothesis appears to be supported by our findings on the presumptions that hexamethonium bromide is a specific ganglionic blocker which inhibits the efferent (postganglionic) transmissions (Leff, White, Munoz, Popovich, Shioya & Stimler-Gerard, 1987) and that ipratropium bromide is a specific muscarinic antagonist which inhibits the effects of 'acetylcholine' released at the neuroepithelial junction.…”
Section: Discussionsupporting
confidence: 81%
“…The present data show that acetylcholine release contributes to the PAF bronchoconstrictor response, as evidenced by the antagonistic properties 110 VAN DE WEERDT et al of atropine. These findings support results of studies in which atropine was reported to antagonize the effects of PAF in tracheal muscle of dogs (LEFF et al, 1987). Likewise, MUNOZ et al (1991) have demonstrated that PAF has a direct contractile effect on both the central and the peripheral airways of rats and that PAF causes substantial augmentation of muscarinic responsiveness in rat pulmonary airways (BETHEL et al, 1989;MUNOZ et al, 1991).…”
Section: Discussionsupporting
confidence: 77%
“…In the dog and rabbit, parasympathetic activation within the airways was recently demonstrated to play a significant role in the airway responses to other bronchoconstrictor agents, e.g. histamine, platelet activating factor (PAF) and substance P (Shore et al, 1985;Leff et al, 1987;Grunstein et al, 1984). As regards PAF and substance P, parasympathetic activation within the airways appears to be the sole contribution of the parasympathetic system to their bronchoconstrictor effects.…”
Section: Discussionmentioning
confidence: 99%